KEPUASAN KERJA, KOMITMEN ORGANISASI, KEPEMIMPINAN, BUDAYA ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Hermanto, Heri; Heriyanto, Meyzi; Karneli, Okta (Jurnal Ilmu Administrasi Negara, 2018)
The Influence of Job Satisfaction, Organizational Commitment, Leadership, Organizational Culture and Organizational Citizenship Behavior (OCB). The objectives of this research are to find out and analyze the Influence of Job Satisfaction, Organizational Commitment, Leadership and Organizational Culture together and partially to OCB. This research type is quantitative approach with survey method dan data analysis have character of statistic/quantitative. Primary data collection through questionnaires to 73 employees at Dinas Kependudukan and Pencacatan Sipil Pekanbaru City, secondar data though company datas related to the problem under study. The method of data analysis used Multiple Linier Regression by using SPSS. The result of research shows that together of variable job satisfaction, Organizational Commitment, Leadership and Organizational Culture influence and significance to OCB employees with value of f artihmetic (17,951) > f table (2,513) and a donations of determination coefficient (R2) 50% meanwhile the rest was 50% influenced by other variable that were not searched in this research.